Differences in survival for patients with familial and sporadic cancer. Issue 3 (3rd November 2016) - Lee, Myeongjee; Reilly, Marie; Lindström, Linda Sofie; Czene, Kamila
Abstract : Family history of cancer is a well‐known risk factor but the role of family history in survival is less clear. The aim of this study was to investigate the association between family history and cancer survival for the common cancers in Sweden. Using the Swedish population‐based registers, patients diagnosed with the most common cancers were followed for cancer‐specific death during 1991–2010. We used multivariate proportional hazards (Cox) regression models to contrast the survival of patients with a family history of cancer (individuals whose parent or sibling had a concordant cancer) to the survival of patients without a family history. Family history of cancer had a modest protective effect on survival for breast cancer (hazard ratio (HR) = 0.88, 95% confidence interval (95% CI) = 0.81 to 0.96) and prostate cancer (HR = 0.82, 95% CI = 0.75 to 0.90). In contrast, family history of cancer was associated with worse survival for nervous system cancers (HR = 1.24, 95% CI = 1.05 to 1.47) and ovarian cancer (HR = 1.20, 95% CI = 1.01 to 1.43). Furthermore, the poorer survival for ovarian cancer was consistent with a higher FIGO stage and a greater proportion of more aggressive tumors of the serous type. The better survival for patients with a family history of breast and prostate cancer may be due to medical surveillance of family members. The poor survival for ovarian cancer patients with an affected mother or sister is multifactorial, suggesting that these cancers are more aggressive than their sporadic counterparts. Abstract : What's new? Family history of cancer is a well‐known risk factor for malignant disease. Yet, whether inherited characteristics, such as variations in therapeutic response, or behavioral factors shared with relatives also influence cancer survival is uncertain. In the present study, the influence of family history on cancer survival was investigated using data from cancer registries in Sweden. Analyses show that family history is a prognostic factor for cancers of certain histological types and at certain anatomical sites. In particular, family history played a protective role in breast and prostate cancer survival but was associated with poor survival in ovarian cancer.